The influence of castillian as roofing language on the Fala from Xalima-Ellas (Caceres) - Flores, Ana Alicia Manso [UNESP]; Conde, Valeria Gil (Univ Sao Paulo, Fac Filosofia, 2022)
Val de Xalima 'Valle de Jalama' or Val do Ellas has the particularity of housing a linguistic variety known as Fala, Valego or Xalimego. This enclave in northwestern Extremadura, bordering Salamanca and Portugal, is formed by the villages of Valverde del Fresno, Eljas and San Martin de Trevejo, where this variety, by adopting particular characters, is called valverdeiru , lagarteiru and manegu , respectively. The study of its structure allows ascribing it to the Galician-Portuguese abstand, although contact with other languages and dialects explains other features. With these precedents, the results from a corpus of eight hundred headwords will be shown from a work of own elaboration. This was obtained through dialect surveys proposed to thirty informants of different sex and age. Especially, cases where the pressure of the roofing language has caused phonetic, morphological or lexical change will be studied. Thus, the tendency to lexical substitution will become evident, more pronounced as the age of the speaker decreases.
Keywords: Val de Xalima-Ellas; Fala; Lexical; Change in progress; Resistance